The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1159/000169926
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Changes in Hemodialysis

Abstract: When chronic renal failure becomes advanced, the serum or tissue levels and/or the functions of most hormones are altered because of several interplaying mechanisms involving synthesis, transport, accumulation of inhibitors, abnormality of target organ responsiveness, and impaired renal clearance. As regular dialysis treatment is performed, most of these uremic hormone abnormalities are not reversed, and some of them may even get worse. The main endocrine derangements can be grouped as sexual hormone dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1990
1990
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…Os relatos mais antigos das dosagens de estrógeno e progesterona nas mulheres em diálise mostravam diminuição desses dois hormônios e chegavam a sugerir uma insuficiência ovariana 8,9,26,18 , enquanto os mais recentes descrevem níveis normais de estró-geno e portanto, sugerem função ovariana intacta 23,24,19 , embora haja relato de que 30% das mulheres pré-menopausadas apresentam hipoestrogenismo 20 . Essas alterações hormonais não se modificam nas fases finais da IRC, ou seja, antes, nas fases iniciais ou após anos de diálise 27,21,28,24 , embora algumas mulheres voltem a menstruar após o início da terapêutica dialítica 29,5,30 . O tipo de diálise (hemodiálise versus diálise peritoneal ambulatorial contínua) não interfere no padrão hormonal 31 , assim como os níveis dos diferentes hormônios não mostram diferenças significantes antes e depois da sessão de hemodiálise 26,32 .…”
Section: Discussionunclassified
“…Os relatos mais antigos das dosagens de estrógeno e progesterona nas mulheres em diálise mostravam diminuição desses dois hormônios e chegavam a sugerir uma insuficiência ovariana 8,9,26,18 , enquanto os mais recentes descrevem níveis normais de estró-geno e portanto, sugerem função ovariana intacta 23,24,19 , embora haja relato de que 30% das mulheres pré-menopausadas apresentam hipoestrogenismo 20 . Essas alterações hormonais não se modificam nas fases finais da IRC, ou seja, antes, nas fases iniciais ou após anos de diálise 27,21,28,24 , embora algumas mulheres voltem a menstruar após o início da terapêutica dialítica 29,5,30 . O tipo de diálise (hemodiálise versus diálise peritoneal ambulatorial contínua) não interfere no padrão hormonal 31 , assim como os níveis dos diferentes hormônios não mostram diferenças significantes antes e depois da sessão de hemodiálise 26,32 .…”
Section: Discussionunclassified
“…First, the re sults of the present study also showed that PTE adminis tration to animals with normal renal function is also associated with a significant decrease in the serum levels of testosterone. Second, suppression of the parathyroid gland activity by administration of 1,25-(OH)2Dj in patients with chronic renal failure was associated with a rise in the serum levels of testosterone [13], It is of interest that the hypotestosteronemia of both acute [2] and chronic [19,20] renal failure is not miti gated by dialysis therapy. These findings indicate that the low serum levels of testosterone in these patients are not due to accumulation of dialyzable toxins.…”
Section: Discussionmentioning
confidence: 99%
“…Carbohydrate intolerance with peripheral insulin resistance usually occurs in uremia [2,13]. Dialysis only partially corrects this metabolic defect.…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%
“…Although usually overshadowed by organ dysfunction and cellular injury caused di rectly by uremic toxins, important endocrine abnormalities occur in uremic patients [2,13]. Renal retention of hormones or inactive immunoreactive fragments, abnormal trans port.…”
mentioning
confidence: 99%